"1.1) \\ \\frac{1}{y^2} \\frac{dy}{dx}+\\frac{1}{y}=2x"
"\\ -\\frac{1}{y^2} \\frac{dy}{dx}-\\frac{1}{y}=-2x"
"v(x)=\\frac{1}{y(x)}, \\ \\frac{dv}{dx}=-\\frac{1}{y^2(x)}\\frac{dy}{dx}"
Substitute "v(x)" :
"\\frac{dv }{dx}-v=-2x"
Multiply by "e^{-x}" both sides of equation:
"e^{-x}\\frac{dv}{dx} -e^{-x}v=-2xe^{-x}"
"e^{-x}\\frac{dv}{dx} +v\\frac{d}{dx}(e^{-x})=-2xe^{-x}"
"\\frac{d}{dx}(ve^{-x})=-2xe^{-x}"
"ve^{-x}=\\int (-2xe^{-x})dx=2xe^{-x}+2e^{-x}+C"
Return to "y(x):"
"\\frac{1}{y}e^{-x}= 2xe^{-x}+2e^{-x}+C"
"y=\\frac{e^{-x}}{2xe^{-x}+2e^{-x}+C}=\\frac{1}{2x+2+Ce^{x}}"
Answer: "y(x)=\\frac{1}{Ce^x+2(x+1)}"
"1.2) (y^2e^{xy^2}+4x^3)dx+(2xye^{xy^2}-3y^2)dy=0"
"P(x,y)=y^2e^{xy^2}+4x^3, \\ \\ Q(x,y)=2xye^{xy^2}-3y^2"
"\\frac{\\partial P(x,y)}{\\partial y} =\\frac{\\partial Q(x,y)}{\\partial x}=2ye^{xy^2}+2xy^3e^{xy^2}"
So, we will find function "f(x,y):"
"\\frac{\\partial f(x,y)}{\\partial x}=y^2e^{xy^2}+4x^3, \\ \\ \\frac{\\partial f(x,y) }{\\partial y}=2xye^{xy^2}-3y^2"
"f(x,y)=\\int (y^2e^{xy^2}+4x^3)dx= e^{xy^2}+x^4+\\phi (y)"
"f(x,y)=\\int (2xye^{xy^2}-3y^2)dy =e^{xy^2} -y^3+\\psi (x)"
"f(x,y)=e^{xy^2}+x^4-y^3"
"\\frac{\\partial f(x,y)}{\\partial x} dx+\\frac{\\partial f(x,y)}{\\partial y} dy=0 \\ \\Rightarrow f(x,y)\\equiv C"
Answer: "e^{xy^2(x)}+x^4-y^3(x)=C"
Comments
Leave a comment